Performance factors in women's team handball: Physical and physiological aspects - A review - Manchado, C.; Tortosa-Martinez, J.; Vila, H.; Ferragut, C.; Platen, P. (The Journal of Strength and Conditioning Research, 2013)
Team handball is an Olympic sport played professionally in many European countries. Nevertheless, a scientific knowledge regarding women's elite team handball demands is limited. Thus, the purpose of this article was to review a series of studies (n = 33) on physical characteristics, physiological attributes, physical attributes, throwing velocity, and on-court performances of women's team handball players. Such empirical and practical information is essential to design and implement successful short-term and long-term training programs for women's team handball players. Our review revealed that (a) players that have a higher skill level are taller and have a higher fat-free mass; (b) players who are more aerobically resistant are at an advantage in international level women team handball; (c) strength and power exercises should be emphasized in conditioning programs, because they are associated with both sprint performance and throwing velocity; (d) speed drills should also be implemented in conditioning programs but after a decrease in physical training volume; (e) a time-motion analysis is an effective method of quantifying the demands of team handball and provides a conceptual framework for the specific physical preparation of players. According to our results, there are only few studies on on-court performance and time-motion analysis for women's team handball players, especially concerning acceleration profiles. More studies are needed to examine the effectiveness of different training programs of women's team handball players' physiological and physical attributes.